Identification of Putative Markers of Non-infectious Bud Failure in Almond [Prunus dulcis (Mill.) D.A. Webb] Through Genome Wide DNA Methylation Profiling and Gene Expression Analysis in an Almond × Peach Hybrid Population - D’Amico-Willman, Katherine M.; Sideli, Gina M.; Allen, Brian J.; Anderson, Elizabeth S.; Gradziel, Thomas M.; Fresnedo-Ramírez, Jonathan (Frontiers in Plant Science, 2022)
Almond [Prunus dulcis (Mill.) D.A. Webb] is an economically important nut crop susceptible to the genetic disorder, Non-infectious Bud Failure (NBF). Despite the severity of exhibition in several prominent almond cultivars, no causal mechanism has been identified underlying NBF development. The disorder is hypothesized to be associated with differential DNA methylation patterns based on patterns of inheritance (i.e., via sexual reproduction and clonal propagation) and previous work profiling methylation in affected trees. Peach (Prunus persica L. Batsch) is a closely related species that readily hybridizes with almond; however, peach is not known to exhibit NBF. A cross between an NBF-exhibiting ‘Carmel’ cultivar and early flowering peach (‘40A17’) produced an F1 where ∼50% of progeny showed signs of NBF, including canopy die-back, erratic branching patterns (known as “crazy-top”), and rough bark. In this study, whole-genome DNA methylation profiles were generated for three F1 progenies exhibiting NBF and three progenies considered NBF-free. Subsequent alignment to both the almond and peach reference genomes showed an increase in genome-wide methylation levels in NBF hybrids in CG and CHG contexts compared to no-NBF hybrids when aligned to the almond genome but no difference in methylation levels when aligned to the peach genome. Significantly differentially methylated regions (DMRs) were identified by comparing methylation levels across the genome between NBF- and no-NBF hybrids in each methylation context. In total, 115,635 DMRs were identified based on alignment to the almond reference genome, and 126,800 DMRs were identified based on alignment to the peach reference genome. Nearby genes were identified as associated with the 39 most significant DMRs occurring either in the almond or peach alignments alone or occurring in both the almond and peach alignments. These DMR-associated genes include several uncharacterized proteins and transposable elements. Quantitative PCR was also performed to analyze the gene expression patterns of these identified gene targets to determine patterns of differential expression associated with differential DNA methylation. These DMR-associated genes, particularly those showing corresponding patterns of differential gene expression, represent key targets for almond breeding for future cultivars and mitigating the effects of NBF-exhibition in currently affected cultivars.